The FpPPR1 Gene Encodes a Pentatricopeptide Repeat Protein That Is Essential for Asexual Development, Sporulation, and Pathogenesis in Fusarium pseudograminearum - Wang, Limin; Xie, Shunpei; Zhang, Yinshan; Kang, Ruijiao; Zhang, Mengjuan; Wang, Min; Li, Haiyang; Chen, Linlin; Yuan, Hongxia; Ding, Shengli; Liang, Shen; Li, Honglian (Frontiers in Genetics, 2021)
Fusarium crown rot (FCR) and Fusarium head blight (FHB) are caused by Fusarium pseudograminearum and are newly emerging diseases of wheat in China. In this study, we characterized FpPPR1, a gene that encodes a protein with 12 pentatricopeptide repeat (PPR) motifs. The radial growth rate of the ΔFpppr1 deletion mutant was significantly slower than the wild type strain WZ-8A on potato dextrose agar plates and exhibited significantly smaller colonies with sector mutations. The aerial mycelium of the mutant was almost absent in culture tubes. The ΔFpppr1 mutant was able to produce spores, but spores of abnormal size and altered conidium septum shape were produced with a significant reduction in sporulation compared to wild type. ΔFpppr1 failed to cause disease on wheat coleoptiles and barley leaves using mycelia plugs or spore suspensions. The mutant phenotypes were successfully restored to the wild type levels in complemented strains. FpPpr1-GFP signals in spores and mycelia predominantly overlapped with Mito-tracker signals, which substantiated the mitochondria targeting signal prediction of FpPpr1. RNAseq revealed significant transcriptional changes in the ΔFpppr1 mutant with 1,367 genes down-regulated and 1,333 genes up-regulated. NAD-binding proteins, thioredoxin, 2Fe-2S iron-sulfur cluster binding domain proteins, and cytochrome P450 genes were significantly down-regulated in ΔFpppr1, implying the dysfunction of mitochondria-mediated reductase redox stress in the mutant. The mating type idiomorphic alleles MAT1-1-1, MAT1-1-2, and MAT1-1-3 in F. pseudograminearum were also down-regulated after deletion of FpPPR1 and validated by real-time quantitative PCR. Additionally, 21 genes encoding putative heterokaryon incompatibility proteins were down-regulated. The yellow pigmentation of the mutant was correlated with reduced expression of PKS12 cluster genes. Taken together, our findings on FpPpr1 indicate that this PPR protein has multiple functions in fungal asexual development, regulation of heterokaryon formation, mating-type, and pathogenesis in F. pseudograminearum.